LASSO-derived prognostic model predicts cancer-specific survival in advanced pancreatic ductal adenocarcinoma over 50 years of age: a retrospective study of SEER database research - Feng, Yuan; Yang, Junjun; Duan, Wentao; Cai, Yu; Liu, Xiaohong; Peng, Yong (Frontiers in Oncology, 2024)
The purpose of this study was to develop a prognostic model for patients with advanced ductal adenocarcinoma aged ≥50 years.: Information on patients was extracted from the Surveillance, Epidemiology and End Results (SEER) database. The least absolute shrinkage and selection operator (LASSO) Cox regression analysis was performed to screen the model variables. Cases from Nanchang Central Hospital were collected as an external validation. The new nomogram and the American Joint Committee on Cancer (AJCC) criteria were evaluated through integrated discrimination improvement (IDI) and net reclassification index (NRI) indicators. Survival curves were presented the prognosis of the new classification system and AJCC criteria. Results: 17,621 eligible patients were included in the study. Lasso Cox regression selected 4 variables including age, chemotherapy, radiotherapy and AJCC stage. The training cohort C-index was 0.721. The validation cohort C-index was 0.729. The AUCs for the training cohort at 1, 2 and 3 years were 0.749, 0.729 and 0.715. The calibration curves showed that the predicted and actual probabilities at 1, 2 and 3 years matched. The external validation similarly confirmed the outstanding predictive power of the model. The decision curve analysis indicated that the clinical benefit of the nomogram was higher than the AJCC staging. The model evaluation indices preceded the AJCC staging with evaluated NRI (1-year: 0.88; 2-year: 0.94; 3-year: 0.72) and IDI (1-year: 0.24; 2-year: 0.23; 3-year: 0.22). The Kaplan-Meier curves implied that the new classification system is more capable of distinguishing between patients at different risks. Conclusions: This study established a prognostic nomogram and risk classification system for advanced pancreatic cancer at age ≥50 years to provide a practical tool for the clinical management of patients with pancreatic ductal adenocarcinoma.